The Evolutionary Origin of C(4) Photosynthesis in the Grass Subtribe Neurachninae - Khoshravesh, Roxana (Plant Physiol, 2020)
The Australian grass subtribe Neurachninae contains closely related species that use C(3), C(4), and C(2) photosynthesis. To gain insight into the evolution of C(4) photosynthesis in grasses, we examined leaf gas exchange, anatomy and ultrastructure, and tissue localization of Gly decarboxylase subunit P (GLDP) in nine Neurachninae species. We identified previously unrecognized variation in leaf structure and physiology within Neurachne that represents varying degrees of C(3)–C(4) intermediacy in the Neurachninae. These include inverse correlations between the apparent photosynthetic carbon dioxide (CO(2)) compensation point in the absence of day respiration (C(*)) and chloroplast and mitochondrial investment in the mestome sheath (MS), where CO(2) is concentrated in C(2) and C(4) Neurachne species; width of the MS cells; frequency of plasmodesmata in the MS cell walls adjoining the parenchymatous bundle sheath; and the proportion of leaf GLDP invested in the MS tissue. Less than 12% of the leaf GLDP was allocated to the MS of completely C(3) Neurachninae species with C(*) values of 56–61 μmol mol(−1), whereas two-thirds of leaf GLDP was in the MS of Neurachne lanigera, which exhibits a newly-identified, partial C(2) phenotype with C(*) of 44 μmol mol(−1). Increased investment of GLDP in MS tissue of the C(2) species was attributed to more MS mitochondria and less GLDP in mesophyll mitochondria. These results are consistent with a model where C(4) evolution in Neurachninae initially occurred via an increase in organelle and GLDP content in MS cells, which generated a sink for photorespired CO(2) in MS tissues.